Passive immunization does not provide protection against experimental infection with Mycoplasma haemofelis. (December 2016) - Sugiarto, Sarah; Spiri, Andrea; Riond, Barbara; Novacco, Marilisa; Oestmann, Angelina; Miranda, Luisa; Meli, Marina; Boretti, Felicitas; Hofmann-Lehmann, Regina; Willi, Barbara
Abstract Mycoplasma haemofelis (Mhf ) is the most pathogenic feline hemotropic mycoplasma. Cats infected withMhf that clear bacteremia are protected fromMhf reinfection, but the mechanisms of protective immunity are unresolved. In the present study we investigated whether the passive transfer of antibodies fromMhf -recovered cats to naïve recipient cats provided protection against bacteremia and clinical disease following homologous challenge withMhf ; moreover, we characterized the immune response in the recipient cats. Ten specified pathogen-free (SPF) cats were transfused with pooled plasma from cats that had clearedMhf bacteremia; five control cats received plasma from naïve SPF cats. After homologous challenge withMhf, cats were monitored for 100 days using quantitative PCR, hematology, blood biochemistry, Coombs testing, flow cytometry, DnaK ELISA, and red blood cell (RBC) osmotic fragility (OF) measurement. Passively immunized cats were not protected againstMhf infection but, compared to control cats, showed significantly higher RBC OF and B lymphocyte (CD45R/B220+ ) counts and occasionally higher lymphocyte, monocyte and activated CD4+ T lymphocyte (CD4+ CD25+ ) counts; they also showed higher bilirubin, total protein and globulin levels compared to those of control cats. At times of peak bacteremia, a decrease in eosinophils and lymphocytes, as well as subsets thereof (B lymphocytes and CD5+, CD4+ and CD8+ T lymphocytes), and an increase in monocytes were particularly significant in the passively immunized cats. In conclusion, passive immunization does not prevent bacteremia and clinical disease following homologous challenge withMhf, but enhances RBC osmotic fragility and induces a pronounced immune response.